2020
DOI: 10.1016/j.hlc.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Initiation During Hospital Admissions for Atrial Fibrillation in South-East Queensland, Australia

Abstract: BACKGROUNDAnticoagulation reduces stroke risk in patients with atrial fibrillation (AF) but underprescribing in eligible patients has been commonly reported. Introduction of the direct acting oral anticoagulants (DOACs) was considered to potentially improve prescribing due to increased anticoagulant options. At the time of release to the Australian market, there was limited studies investigating anticoagulant usage during hospitalisations for AF. Therefore, the aim of this study was to investigate prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…[32,35,43,70,73,83] Stroke and bleeding risk or history are important predictors of guideline non-adherence and non-prescription of OACs. As one might expect, risk [36,43,76] or history of [58,83] stroke is directly associated with prescription of OACs, while bleeding risk [58,70,76] or previous bleeding [32,35,36,43,77] has an inverse association.…”
Section: Patient-related Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…[32,35,43,70,73,83] Stroke and bleeding risk or history are important predictors of guideline non-adherence and non-prescription of OACs. As one might expect, risk [36,43,76] or history of [58,83] stroke is directly associated with prescription of OACs, while bleeding risk [58,70,76] or previous bleeding [32,35,36,43,77] has an inverse association.…”
Section: Patient-related Factorsmentioning
confidence: 97%
“…[40] When it comes to overtreatment, between 0.6% and 79.8% of patients at low risk of stroke who did not need any antithrombotic medication received treatment, which would be considered to be overtreatment. [18,22,26,31,33,35,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Recent studies that investigated trends in guideline adherence have shown substantial improvements in guideline adherence over time. Cowan et al [63] reported an increase in the prescription of OACs (by 30.6%) and a decline in the prescription of antiplatelet agents (by 26.8%) over a 10-year period in AF patients at high risk of stroke.…”
Section: Non-adherence To Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors contribute to OAC undertreatment in AF. Most of the previous studies that reported factors associated with thromboprophylaxis undertreatment in AF were based on findings from retrospective studies and largely outside of the general practice setting 7,10,13–15 . Nonetheless, a previous review article identified that prescriber‐related factors, including their beliefs and practice patterns, were among the major contributors 8 .…”
Section: Introductionmentioning
confidence: 99%